2013
DOI: 10.1111/j.1476-5381.2012.02174.x
|View full text |Cite
|
Sign up to set email alerts
|

AKAP‐dependent sensitization ofCav3.2 channels via theEP4receptor/cAMPpathway mediatesPGE2‐induced mechanical hyperalgesia

Abstract: BACKGROUND AND PURPOSEThe Cav3.2 isoform of T-type Ca 2+ channels (T channels) is sensitized by hydrogen sulfide, a pro-nociceptive gasotransmitter, and also by PKA that mediates PGE2-induced hyperalgesia. Here we examined and analysed Cav3.2 sensitization via the PGE2/cAMP pathway in NG108-15 cells that express Cav3.2 and produce cAMP in response to PGE2, and its impact on mechanical nociceptive processing in rats. EXPERIMENTAL APPROACHIn NG108-15 cells and rat dorsal root ganglion (DRG) neurons, T-channel-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 58 publications
(94 reference statements)
0
15
1
1
Order By: Relevance
“…Past work conducted in cardiac and neuronal tissues has consistently shown that T-type Ca 2+ channels are a rich target for protein kinase regulation (Li et al, 2012;Sekiguchi et al, 2013). Of particular note is the reported ability of PKA through receptor stimulation to selectively augment Ca V 3.1 or Ca V 3.2 activity in a tissue-dependent manner (Li et al, 2012;Sekiguchi et al, 2013).…”
Section: Protein Kinase Regulation Of Voltage-gated Ca 2+ Channelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Past work conducted in cardiac and neuronal tissues has consistently shown that T-type Ca 2+ channels are a rich target for protein kinase regulation (Li et al, 2012;Sekiguchi et al, 2013). Of particular note is the reported ability of PKA through receptor stimulation to selectively augment Ca V 3.1 or Ca V 3.2 activity in a tissue-dependent manner (Li et al, 2012;Sekiguchi et al, 2013).…”
Section: Protein Kinase Regulation Of Voltage-gated Ca 2+ Channelsmentioning
confidence: 99%
“…Of particular note is the reported ability of PKA through receptor stimulation to selectively augment Ca V 3.1 or Ca V 3.2 activity in a tissue-dependent manner (Li et al, 2012;Sekiguchi et al, 2013). In vascular smooth muscle, PKA signaling plays a prominent role in enabling vasodilation through mechanisms involving reductions in cytosolic Ca 2+ .…”
Section: Protein Kinase Regulation Of Voltage-gated Ca 2+ Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). AKAP-dependent functional upregulation of Ca v 3.2 by PKA following EP 4 receptor activation mediates PGE 2 -induced mechanical hyperalgesia (15), although sensitization of TRPV1 channels by PKC following EP 1 -receptor activation participates in the PGE 2 -induced thermal hyperalgesia (24) (Fig. 2).…”
Section: Somatic Pain Processing By T-channelsmentioning
confidence: 99%